Сходимость процессов нейродинамики в модели Хопфилда - Шатырко, А.В.; Диблик, Й.; Хусаинов, Д.Я.; Баштинец, Я. (Штучний інтелект, 2017)
Рассматриваются математические модели динамики нейронной сети, представленные системами обыкновенных дифференциальных уравнений, а также дифференциальных уравнений с запаздыванием c выделенной асимптотически устойчивой линейной частью диагонального вида. С использованием прямого метода Ляпунова получены достаточные условия асимптотической устойчивости. Результаты сформулированы в виде матричных алгебраических неравенств. Mathematical models of the dynamics of a neural network, which are represented by systems of ordinary differential equations, as well as differential equations with time-delay argument and the distinguished asymptotically stable linear part are considered. With the using of the direct Lyapunov method, sufficient conditions for asymptotic stability are obtained and exponential estimates of the solutions decay are constructed. The results are formulated in the form of matrix algebraic inequalities.